2018
DOI: 10.1007/s00705-018-3909-4
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric-pressure plasma irradiation can disrupt tobacco mosaic virus particles and RNAs to inactivate their infectivity

Abstract: Low-temperature atmospheric-pressure air plasma is a source of charged and neutral gas species. In this study, N-carrying tobacco plants were inoculated with plasma irradiated and non-irradiated tobacco mosaic virus (TMV) solution, resulting in necrotic local lesions on non-irradiated, but not on irradiated, TMV-inoculated leaves. Virus particles were disrupted by plasma irradiation in an exposure-dependent manner, but the viral coat protein subunit was not. TMV RNA was also fragmented in a time-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…CP is produced by applying an electrical charge to a gas, which ionizes the gas to produce a mixture of excited molecules, charged particles, reactive oxygen and nitrogen species, and some UV light and ozone. As such it has unique antimicrobial properties that have been demonstrated to be effective against plant pathogenic bacteria (Moreau et al , ), and also tobacco mosaic virus (Hanbal et al , ). CP studies on common postharvest fungi such as Aspergillus parasiticus , A. oryzae and Penicillium digitatum have reported optimistic results, with up to 100% control following CP treatment of contaminated nuts (hazelnut, peanut and pistachio; Basaran et al , ), grains (wheat, barley and rice; Selcuk et al , ; Hayashi et al , ) and fruit (lemon and mandarin; Hayashi et al , ; Won et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…CP is produced by applying an electrical charge to a gas, which ionizes the gas to produce a mixture of excited molecules, charged particles, reactive oxygen and nitrogen species, and some UV light and ozone. As such it has unique antimicrobial properties that have been demonstrated to be effective against plant pathogenic bacteria (Moreau et al , ), and also tobacco mosaic virus (Hanbal et al , ). CP studies on common postharvest fungi such as Aspergillus parasiticus , A. oryzae and Penicillium digitatum have reported optimistic results, with up to 100% control following CP treatment of contaminated nuts (hazelnut, peanut and pistachio; Basaran et al , ), grains (wheat, barley and rice; Selcuk et al , ; Hayashi et al , ) and fruit (lemon and mandarin; Hayashi et al , ; Won et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral effects of plasma have been occasionally demonstrated in human and animal viruses, as well as bacteriophages (Zimmermann et al, 2011;Aboubakr et al, 2015;Guo et al, 2018). The inactivation of plant viruses by plasma was demonstrated in a recent study (Hanbal et al, 2018). In this study, inoculation with plasma irradiated tobacco mosaic virus (TMV) solution did not induce the development of disease in tobacco plants, whereas necrotic local lesions developed on tobacco leaves inoculated with non-irradiated TMV solution (Hanbal et al, 2018).…”
Section: Viral Pathogensmentioning
confidence: 66%
“…The inactivation of plant viruses by plasma was demonstrated in a recent study (Hanbal et al, 2018). In this study, inoculation with plasma irradiated tobacco mosaic virus (TMV) solution did not induce the development of disease in tobacco plants, whereas necrotic local lesions developed on tobacco leaves inoculated with non-irradiated TMV solution (Hanbal et al, 2018). Min et al (2016) also showed that viral load was significantly reduced when romaine lettuce inoculated with Tulane virus was treated with DBD plasma.…”
Section: Viral Pathogensmentioning
confidence: 68%
“…none of these studies considered virus inactivation for water decontamination. Only two studies in the CAP-virus field have assessed the inactivation of viruses in larger volumes of water (Guo et al, 2018;Filipić et al, 2019), and only two have reported on the applications of CAP for inactivation of plant viruses, including potato virus Y (PVY; Filipić et al, 2019) and tomato mosaic virus (Hanbal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%